Pengembangan Pembelajaran Sosial Emosional Melalui Game Based Learning Berbantuan Gimkit - Alfia Nuri Aliantari; Lady Agustina (Jurnal Inovasi Pendidikan Matematika (JIPM), 2025)
This study aims to analyze social-emotional learning in mathematics learning through game-based learning assisted by Gimkit. Based on the challenges of the 21st century, it is not enough to have cognitive aspects; it is also necessary to possess good social-emotional abilities. The research employs the Research and Development (R&D) method, utilizing the ADDIE development model, which encompasses the analysis, design, development, implementation, and eval_uation stages. The research was conducted at SMAN Mumbulsari Jember with students in class XI.3 as subjects. Learning is designed in groups, and students develop strategies to solve challenges. In its implementation, this learning can improve students’ social-emotional abilities. Students practice controlling emotions and accepting defeat, and also work together to determine strategies to win the game. In this game, they also practice having empathy for friends. Students also feel motivated to learn mathematics because learning with Gimkit is very interesting and fun. This study demonstrates that learning with Gimkit can enhance students’ social-emotional abilities, specifically self-awareness, self-management, social awareness, relationship skills, and responsible decision-making.